A Logistic Regression Model to Assess Factors Influencing Schizophrenia Symptoms in Namibia - Nakunipa, E. N.N.; Pazvakawambwa, L; Iiyambo, P (Namibian Journal for Research, Science and Technology, 2022)
Schizophrenia is a common mental disorder in Namibia and affects about 20 million people worldwide. Risk factors for schizophrenia in Namibia have not been extensively investigated. The objective of the study was to establish prevalence and factors influencing schizophrenia symptoms based on secondary data from the 2013 Namibia Demographic and Health Survey (NDHS). Descriptive statistics were computed to profile the background characteristics of the sample. Chi-square tests were conducted to assess association between socio-demographic variables and schizophrenia symptoms. Binary logistic regression was performed to establish determinants of schizophrenia symptoms. The prevalence of schizophrenia symptoms was 12.4% (13.6% among females and 11.0% among males). Regression results indicated that females (OR=1.159, 95% CI: 1.022-1.314, p=0.021) were more likely to have schizophrenia symptoms compared to their male counterparts. Those who resided in urban areas (OR=0.699, 95% CI: 0.609-0.803, p<0.001) were less likely to have schizophrenia symptoms compared to those who resided in rural areas. Those with no formal education (OR=0.378, 95% 0.273-0.523, p<0.001); those with primary education (OR=0.646, 95% CI: 0.501-0.834, p<0.001) and those with secondary education (OR=0.619, 95% CI: 0.495-0.775, p<0.001) were less likely to have schizophrenia symptoms compared to those with higher education. Results also showed that those who had never married (OR=0.275, 95% CI: 0.225-0.335, p<0.001); the married (OR=0.229, 95% CI: 0.184-0.284, p<0.001); and those living with a partner (OR=0.283, 95% CI: 0.225-0.355, p<0.001) were less likely to have schizophrenia symptoms compared to those who were on separation. Respondents who did not consume alcoholic drinks (OR=0.597, 95% CI: 0.526-0.677, p<0.001) were less likely to have schizophrenia symptoms compared to those who consumed alcoholic drinks. Schizophrenia symptoms were not significantly influenced by wealth index (p>0.05). There is need to step up gender-specific mental health programs especially in rural areas. Efforts to stabilize marital relationships at national level should be strengthened. Mental health could also be improved through drug abuse prevention and rehabilitation programs.